Unpaid Caregiving Roles and Sleep Among Women Working in Nursing Homes: A Longitudinal Study. (19th January 2018) - DePasquale, Nicole; Sliwinski, Martin J; Zarit, Steven H; Buxton, Orfeu M; Almeida, David M
Abstract: Background and Objectives: Although sleep is a critical health outcome providing insight into overall health, well-being, and role functioning, little is known about the sleep consequences of simultaneously occupying paid and unpaid caregiving roles. This study investigated the frequency with which women employed in U.S.-based nursing homes entered and exited unpaid caregiving roles for children (double-duty-child caregivers), adults (double-duty-elder caregivers), or both (triple-duty caregivers), as well as examined how combinations of and changes in these caregiving roles related to cross-sectional and longitudinal sleep patterns. Research Design and Methods: The sample comprised 1, 135 women long-term care employees who participated in the baseline wave of the Work, Family, and Health Study and were assessed at three follow-up time points (6-, 12-, and 18-months). Sleep was assessed with items primarily adapted from the Pittsburgh Sleep Quality Index and wrist actigraphic recordings. Multilevel models with data nested within persons were applied. Results: Women long-term care employees entered and exited the unpaid elder caregiving role most frequently. At baseline, double-duty-child and triple-duty caregivers reported shorter sleep quantity and poorer sleep quality than their counterparts without unpaid caregiving roles, or workplace-only caregivers. Double-duty-elder caregivers also reported shorter sleep duration compared to workplace-only caregivers. Over time, double-duty-elder caregiving role entry was associated with negative changes in subjective sleep quantity and quality. Discussion and Implications: Simultaneously occupying paid and unpaid caregiving roles has negative implications for subjective sleep characteristics. These results call for further research to advance understanding of double-and-triple-duty caregivers' sleep health and facilitate targeted intervention development.